PEMBERDAYAAN KELOMPOK BIDAN EBSCO TENTANG GIZI DAN HIDRASI MELALUI APLIKASI “PERISAI BUMIL-PLUS - Erry Yudhya Mulyani; Mariyana; Nizirwan Anwar; Anindya Billa Mustika (UII, 2023)
As many as 31.7% of mothers had less knowledge about nutrition and hydration and about 57.1% pregnant women were dehydrated. Currently, the use of technology as an educational medium is important to use in increasing one's knowledge. This activity is an activity in an effort to improve the knowledge, attitudes and skills of midwives in providing information to pregnant women by utilizing the educational media application